Pengaruh Penggunaan Artificial Intelligence (AI) dan Problem Based Learning Terhadap Kemampuan Berpikir Kritis Mahasiswa pada Mata Kuliah Fikih di IAIN Bone - Fani Rahmasari; Kasmah; Arisal A (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the effect of the use of Artificial Intelligence (AI) and Problem Based Learning (PBL) on students' critical thinking skills in the Fiqh course at IAIN Bone. The study used a quantitative approach with an ex post facto correlational design. The study population was 708 students who had taken the Fiqh course, with a sample of 255 respondents selected using stratified random sampling techniques. Data collection was carried out through questionnaires, while data analysis used descriptive statistics, inferential learning, and multiple linear regression with the help of SPSS. The results showed that the use of AI had a positive but not significant effect on students' critical thinking skills (Sig. 0.285 > 0.05). Conversely, PBL had a positive and significant effect on critical thinking skills (Sig. 0.001 < 0.05). Simultaneously, AI and PBL had a significant effect on critical thinking skills with an F value of 19.065 and a significance of 0.000. However, the coefficient of determination (R²) of 0.131 indicates that the two variables only explain 13.1% of the variation in critical thinking skills, with the remainder influenced by factors outside the study. This finding suggests that strengthening students' critical thinking skills is more effective through the integration of technology with active, problem-solving learning approaches such as PBL.